Building the capacity of Kenya's farmer organisations - Rutere, Gervasio (Technical Centre for Agricultural and Rural Cooperation, 2018)
To increase the capacity of the Kenya Livestock Producers Association (KLPA), a team of national and international organisations mentored the organisation. As a result of the capacity building programme, the skills and knowledge of KLPA staff have grown, and the organisation's policies have been strengthened.